A near infrared light-triggerable modular formulation for the delivery of small biomolecules - Francisco, Vitor (2019)
Background: Externally triggered drug delivery systems hold considerable promise for improving the treatment of many diseases, in particular, diseases where the spatial-temporal release of the drug is critical to maximize their biological effect whilst minimizing undesirable, off-target, side effects. Results: Herein, we developed a light-triggerable formulation that takes advantage of hostguest chemistry to complex drugs functionalized with a guest molecule and release it after exposure to near infrared (NIR) light due to the disruption of the non-covalent host-guest interactions. The system is composed by a gold nanorod (AuNR), which generates plasmonic heat after exposure to NIR, a thin layer of hyaluronic acid immobilized to the AuNR upon functionalization with a macrocycle, cucurbit[6]uril (CB[6]), and a drug functionalized with a guest molecule that interacts with the macrocycle. For proof of concept, we have used this formulation for the intracellular release of a derivative of retinoic acid (RA), a molecule known to play a key role in tissue development and homeostasis as well as during cancer treatment. We showed that the formulation was able to conjugate approximately 65 μg of RA derivative per mg of CB[6]@AuNR and released it within a few minutes after exposure to a NIR laser. Importantly, the bioactivity of RA released from the formulation was demonstrated in a reporter cell line expressing luciferase under the control of the RA receptor. Conclusions: This NIR light-triggered supramolecular-based modular platform holds great promise for theranostic applications.